Pandangan Generasi Muda Terkini tentang Kerukunan Umat Beragama: Kasus Komparatif Semarang dan Yogyakarta: The Views of the Current Young Generation on Religious Harmony: Comparative Cases Between Semarang and Yogyakarta - Jati, Wasisto (Jurnal Bimas Islam, 2025)
Indonesia has a long-standing history of religious harmony, as manifested in its diverse expressions of local wisdom and socio-religious norms. The presence of these indigenous values, coupled with the integration of religious and cultural practices, has fostered a harmonious and peaceful society. Nevertheless, this process has been disrupted, leading to the development of tolerance and, subsequently, restrictions on the state's capacity to regulate interactions among religious communities in public areas. Young people's acknowledgment of these issues has facilitated their contribution to religious harmony within their communities. A pertinent area for further discussion is the younger generation's perspective on religious harmony. This study employed a qualitative research design, utilizing in-depth interviews conducted in Yogyakarta and Semarang. Findings indicate that younger generations' perspectives on religious harmony are fundamentally rooted in inclusivity and a willingness to embrace diversity. This study sought to investigate the perspectives and expressions of young people concerning religious harmony, a subject of growing scholarly interest. This subsequently takes the form of a space designed for meetings and dialogue.